From teacher thinking to teachers and teaching the evolution of a research community - Craig, Cheryl J.; Meijer, Paulien C.; Broeckmans, Jan (Advances in research on teaching, 2013)
This volume covers advances that have occurred in the thirty year existence of the International study association on teachers and teaching (ISATT), the organization that helped transition the study of teacher thinking to the study of teachers and teaching in all of its complexities. This evolution meant that teachers and the act of teaching are no longer exclusively studied from the outside, but from the inside as well. The chapters capture an international paradigm shift that set the course of teaching and teacher education research. The origins of the movement are traced, work of researchers who contributed to the movement is featured, the spread of the movement into new regions is followed, and the future of the international research community that resulted is imagined. Thirteen section editors and the two main editors present the volume by themes, with work from several regions covered in each theme area. Each sub-section includes (1) a representative sample of research conducted historically on a particular topic; (2) a review of what developments have occurred in the interim; and (3) contemporary piece/s of scholarship.